MULTIFACETED DIMENSIONS OF INTEGRATION IN TEACHING ENGLISH FOR NATURAL SCIENCES - Volodymyr Sulym (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The research is aimed at discussing multifaceted dimensions of integration in teaching and learning foreign languages for specific purposes, namely - English for Sciences. The author explored the relevance, necessity, efficiency, and challenges teachers face when teaching students ESP in terms of language and professional content integration. The integrated approach has been viewed as contextualised integration of occupational situations, language and speech activity, involving the necessary speech skills and language habits singled out for each particular situation. The participants of the study were 112 teachers from 6 Ukrainian Universities. Specially designed surveys were used in the experiment. The results demonstrated teachers' positive feedback on questions about the ESP relevance at technical universities. It was found that the course content, educational resources and materials should include that scope of knowledge and skills which will correspond to students' professional as well as communicative needs. It can be achieved by the integration of needs and target occupational situation analysis with the course objectives and its content. With a view of enhancing the integration approach in ESP, the author suggests recommendations to follow for successful implementation of the approach.